Photoreversible Growth of Micropattern. Issue 19 (6th October 2016) - Hou, Honghao; Ma, Xiaodong; Xu, Hongjie; Shi, Zixing; Yin, Jie; Jiang, Xuesong
Abstract : Self‐organized surface patterns from the nano‐ to microscale inspired by nature find wide applications in functional intelligent materials in various fields. In particular, complex patterns with the reversible topographies that do not alter the material's intrinsic properties allow for the possibility of on‐demand control of the surface properties. Herein, a facile strategy is presented to fabricate a micro/nanopatterned surface whose morphology can be changed timely and spatially by light. The complex pattern is fabricated on the surface of a photocuring coating through a one‐step, self‐patterned process, in which self‐assembly of fluorinated azobenzene‐containing polymer and photoreversible isomerization lead to the generation of compressive stress, resulting in the formation of a reversible surface pattern. The reversible change of the pattern morphology allows for light control of the adhesion and wettability of the surface. Moreover, the one‐step approach to fabricate the complex pattern possesses characteristics similar to the formation process of the self‐organizing micro/nanopatterns in nature. The feasibility and generality of this approach for obtaining such bioinspired, photoreversible, and self‐organized patterned surfaces will find wide applications in functional intelligent materials with properties that can be tuned on‐demand without altering the material's intrinsic properties. Abstract : A facile bottom‐up strategy to obtain micropattern able to undergo reversible, homogeneous, and tunable geometrical changes upon photocontrol with variable illuminations is demonstrated. A photoreversible and tunable adhesion and wettability is realized via the photoreversible growth and disappearance of micropattern, which will find wide applications in functional intelligent materials with properties that can be tuned on‐demand without altering the material's intrinsic properties.